“Eu voltei, agora pra ficar!”: um estudo sobre as estratégias empreendedoras adotadas por dekasseguis retornados no Estado do Pará - FERNANDES, José Augusto Lacerda (Universidade Federal do Pará, 2014)
Depending on the importance of business activity for the conduct of return migration, particularly with regard to mitigating the risks and problems typically experienced by the protagonists of such offsets, this thesis aimed to understand and explain the process of formation of entrepreneurial strategies adopted by these immigrants returned to the state of Pará. To this end, we developed an eminently qualitative case study, using a large data set, highlighting the narratives obtained through semi-structured interviews, proceeded not only with individuals who have created business after returning from Japan, but also with managers of organizations involved with the movement dekasseguis in a broader sense. The findings have resulted in a model of very wide analysis and multi-scale character, which promotes a deeper understanding of the migratory trajectories and observed business initiatives, able to capture a series of elements that come together in the design and development process strategies in view. Through it was possible to defend the thesis that: the business strategies adopted by these immigrants returned were formed by combinations of opportunities and constraints existing at each stage of their migratory paths economic, sociocultural and political/institutional character as well, and the spatial context time that her actions were. This reinforces, in turn, the need to use mixed methods and sociological approaches in the study of these phenomena. Besides, of course, providing an interesting set of considerations and recommendations to students of the subject and practitioners from the field, aspiring to be dekasseguis, dekasseguis returnees who have already started their own businesses, leaders nikkey associations, managers of federal and state agencies, among others.